2018
DOI: 10.1039/c8cy00328a
|View full text |Cite
|
Sign up to set email alerts
|

Salt-promoted catalytic methanol carbonylation using iridium pincer-crown ether complexes

Abstract: Iridium complexes of pincer ligands containing aza-crown ether macrocycles are precatalysts for methanol carbonylation. Turnover numbers for all acetyl-containing products could be tuned from 265 to 1950 using metal and tetrabutylammonium salts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…Initial studies investigating the activation of MeOAc by previously reported (NCOP)­Ir­(CO) complexes did not show promising reactivity, despite the ability of these carbonyl complexes to carry out the individual steps and overall catalytic reaction of methanol carbonylation in the presence of methyl iodide. , Inspired by reports from the Goldman group demonstrating net C–O bond activation via initial C–H bond activation, , and our own recent observation of ether decarbonylation via C–H bond activation, we turned to the dinitrogen complex [( MeO‑Et NCOP)­Ir] 2 (μ-N 2 ) ( 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Initial studies investigating the activation of MeOAc by previously reported (NCOP)­Ir­(CO) complexes did not show promising reactivity, despite the ability of these carbonyl complexes to carry out the individual steps and overall catalytic reaction of methanol carbonylation in the presence of methyl iodide. , Inspired by reports from the Goldman group demonstrating net C–O bond activation via initial C–H bond activation, , and our own recent observation of ether decarbonylation via C–H bond activation, we turned to the dinitrogen complex [( MeO‑Et NCOP)­Ir] 2 (μ-N 2 ) ( 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…30 ppm upeld shi of the phosphinite resonance relative to 1 18c6 (from d 143.67 to d 171.32) in the 31 P NMR spectrum provided an early indication that the product was an iridium(I) complex. 13,18 We initially vetted the spectroscopic data against the possibility of iridium(I) complexes with either (a) a tetradentate pincer-crown ether ligand containing one crown ether oxygen bound, (k 4 -MeO-18c6 NCOP)Ir, or (b) a tridentate pincer-crown ether ligand with N 2 completing the square planar coordination sphere, (k 3 -MeO-18c6 NCOP)Ir(N 2 ). However, neither of these structures could be explained by the NMR data.…”
Section: Intramolecular Ether Decarbonylationmentioning
confidence: 99%
“…1D). The new triplet and singlet were assigned as unexpected -OCH 2 CH 3 and -NCH 3 groups, respectively, using a combination of multidimensional NMR experiments, including 1 H-1 H COSY, 1 H- 13 C HSQC and 1 H- 13 C HMBC ( Fig. S42-S44, ESI †).…”
Section: Intramolecular Ether Decarbonylationmentioning
confidence: 99%
“…In the course of this study, we found that adding a methoxy group to the phenyl backbone blocks C-H bond activation pathways that lead to catalyst deactivation. 39,40 Structural comparisons of catalysts with and without "blocking" methoxy groups were therefore sought ( Figure 2). The known hydrido chloride complex with the backbone methoxy group, k 4 -( MeO-18c6 NCOP iPr )Ir(H)(Cl) (1-18c6b), 38 was converted to aqua complex [k 4 -( MeO-18c6 NCOP iPr )Ir(H)(OH2)][BAr F 4] (3-18c6b) and then the desired catalyst [k 5 -( MeO-18c6 NCOP iPr )Ir(H)][BAr F 4] according to Figure 2.…”
Section: Synthesis Of New Catalysts Featuring Aza-18-crown-6mentioning
confidence: 99%